An integrated haptic-enabled virtual reality system for orthognathic surgery planning. Issue 5 (4th April 2019) - Zaragoza-Siqueiros, Jorge; Medellin-Castillo, Hugo I.; de la Garza-Camargo, Héctor; Lim, Theodore; Ritchie, James M.
Abstract: Conventional Orthognathic surgery (OGS) planning involves cephalometric analyses and dental casts to be mounted on an articulator. Dental segments are subsequently identified, cut and repositioned to allow the fabrication of intraoral wafers that guide the positioning of the osteotomy bone segments. This conventional planning introduces many inaccuracies that affect the post-surgery outcomes. Although computer technologies have advanced computational tools for OGS planning, they have failed in providing a practical solution. Many focuses only on some specific stages of the planning process, and their ability to transfer preoperative planning data to the operating room is limited. This paper proposes a new integrated haptic-enabled virtual reality (VR) system for OGS planning. The system incorporates CAD tools and haptics to facilitate a complete planning process and is able to automatically generate preoperative plans. A clinical pre-diagnosis is also provided automatically by the system based on the patient's digital data. A functional evaluation based on a real patient case study demonstrates that the proposed virtual OGS planning method is feasible and more effective than the traditional approach at increasing the intuitiveness and reducing errors and planning times.